Critical Synthesis Package: Tool for Assessing Cultural Competence Training (TACCT) - Jennifer Boardman (Association of American Medical Colleges, 2015)
Abstract This resource contains: (1) a Critical Analysis of the psychometric properties and the application to health science of the Tool for Assessing Cultural Competence Training (TACCT), and (2) a copy of the revised TACCT instrument, scoring key, and manual developed by Desiree Lie, MD, MSED. The TACCT is an easy to use instrument with 42 items divided into various domains based on knowledge, skills, and attitudes. The six domains consist of: health disparities, community strategies, bias/stereotyping, communication skills specific to cross-cultural communication, use of interpreters, and self-reflection/culture of medicine. The measure is intended to be used by faculty to monitor new cultural competence curricular innovations, identify under-addressed curricular areas, and measure faculty and student perceptions regarding a cultural competence curriculum. Strengths of the instrument include: (1) coverage of a broad overview of topics including knowledge, skills, and attitudes impacting cultural competency training for medical students; (2) providing an opportunity to create a detailed blueprint of when and how specific cultural competence topics are being taught and assessed; and, (3) the ability to be self-administered in either a pen-and-paper or electronic format. Conversely, the revised TACCT is still a relatively long survey to complete, there are no recommendations for when the instrument should be administered during a student's tenure, and it does not address any hidden curricula many students may encounter. Moreover, the TACCT aims to address whether or not attitudes are explored in a school's cultural competence curriculum, which is significantly more difficult to measure than knowledge and skills. Despite the limitations, the TACCT can monitor new cultural competence curriculum innovations, identify under-addressed curriculum areas, and measure faculty and student perceptions regarding the curriculum.